Myocardial Ischemia Induced by 5‐Fluorouracil: A Prospective Electrocardiographic and Cardiac Biomarker Study - Dyhl‐Polk, Anne; Schou, Morten; Vistisen, Kirsten K.; Sillesen, Anne‐Sophie; Serup‐Hansen, Eva; Faber, Jens; Klausen, Tobias W.; Bojesen, Stig E.; Vaage‐Nilsen, Merete; Nielsen, Dorte L. (The oncologist (Dayton, Ohio), 2021)
Background Cardiotoxicity induced by 5‐fluorouracil (5‐FU) is well known but poorly understood. In this study, we undertook ECG recording (Holter) and analyses of the biomarkers troponin and copeptin in patients receiving 5‐FU to increase our understanding of the cardiotoxicity. Subjects, Materials, and Methods Patients with colorectal or anal cancer that received first‐time treatment with 5‐FU‐based chemotherapy were prospectively included. Holter recording, clinical evaluation, 12‐lead electrocardiogram, and assessment of plasma concentrations of troponin I and copeptin were performed before (control) and during 5‐FU treatment (intervention). Results A total of 108 patients were included, 82 with colorectal and 26 with anal cancer. The proportion of patients with myocardial ischemia on Holter recording was significantly higher during the first 5‐FU infusion (14.1%) than before (3.7%; p = .001). The ischemic burden per day (p = .001), the number of ST depression episodes per day (p = .003), and the total duration of ischemic episodes per day (p = .003) were higher during the first 5‐FU infusion than before, as was plasma copeptin (p < .001), whereas plasma troponin I was similar (p > 0.999). Six patients (5.6%) developed acute coronary syndromes and two (1.8%) developed symptomatic arrhythmias during 5‐FU treatment. Conclusion 5‐FU infusion is associated with an increase in the number of patients with myocardial ischemia on Holter recording. According to biomarker analyses, 5‐FU is associated with an increase in copeptin, but rarely with increases in cardiac troponin I. However, 5%–6% of the patients developed acute coronary syndromes during treatment with 5‐FU. Implications for Practice Symptomatic 5‐fluorouracil (5‐FU) cardiotoxicity occurs in 0.6%–19% of patients treated with this drug, but a small electrocardiographic (Holter) study has revealed silent myocardial ischemia in asymptomatic patients, suggesting a more prevalent subclinical cardiac influence. This study demonstrated a significant increase in the number of patients with myocardial ischemia on Holter recording during 5‐FU treatment and an increase in ischemic burden. Cardiac biomarker analyses suggested that 5‐FU infusion results in endogenous stress (increased copeptin) but rarely induces myocyte injury (no change in troponin). These findings suggest a more prevalent cardiac influence from 5‐FU and that Holter recording is an important tool in the evaluation of patients with suspected cardiotoxicity from 5‐FU. Cardiotoxicity related to 5‐fluorouracil (5‐FU) treatment is poorly understood. This article reports results of a study using electrocardiogram results to analyze the biomarkers troponin and copeptin in patients receiving 5‐FU.